The Effect of Village Government Competence and Whistleblowing System on the Prevention of Village Fund Fraud with Organizational Culture as a Moderating Variable - Nisa, Maulidatun; Januarti, Indira (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study investigates the effect of village government competence and the whistleblowing system on the prevention of village fund fraud, with organizational culture as a moderating variable. This study employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to respondents involved in village fund management in Central Buton Regency. A total of 67 respondents participated in the study, with a 100% response rate, allowing all data to be processed. The data analysis technique utilized Structural Equation Modeling based on Partial Least Squares. The results indicate that village government competence and the whistleblowing system have a positive effect on the prevention of village fund fraud. However, organizational culture is not proven to moderate the relationship between village government competence and the whistleblowing system on fraud prevention. These findings imply that enhancing village government competence and optimizing the implementation of the whistleblowing system are essential factors in strengthening fraud prevention efforts in village fund management.